Candida dubliniensis breast implant infection in a lung transplant recipient - Ashley Barnes, MD; Kristen Broderick, MD; Errol Bush, MD; Jonathan Orens, MD; Melanie Marashly, CRNP; Shmuel Shoham, MD; Robin Avery, MD (JHLT Open)
This report details the case of a lung transplant recipient with a remote history of breast cancer and breast reconstruction with implants, who received lengthy antifungal therapy for a post-transplant donor-transmitted Candida dubliniensis empyema. Despite this, she presented months later with a progressive infection of bilateral breast implants, which also proved to be due to Candida dubliniensis. Few cases of breast implant infection after lung transplant have been published. It is possible that biofilm created a barrier to penetration of antifungals, which were able to suppress but not eradicate infection. This case highlights the importance of deep operative cultures for diagnosis and management of infections of this type.